Incorporating the concept of overtransfusion into hemovigilance monitoring: An expert-based definition and criteria from the International HIT-OVER Forum - Fischer, Dania; Weigand, Markus A.; Moss, R.; Veiras, S.; Kübel, B.; Garcia-Erce, J. A.; Zacharowski, K.; Meybohm, P.; Waters, J. H.; Raasveld, S. J.; Vlaar, A. P. J.; Richards, T.; et al. (Transfusion, 2025)
Background Liberal or overtransfusion (OT) may be regarded as “inappropriate,” but it is not reported as a transfusion-related adverse event. A definition of OT is lacking. OT may include overdosing of components, giving the incorrect component, or unnecessary administration without evidence of need for transfusion. OT can be associated with hypercoagulability, thrombosis, alloimmunization, increased mortality, longer hospital stay, increased infection rates, and adverse cardiocirculatory events. Study Design and Methods In 2023, an expert panel formed a hemovigilance international taskforce embedded in the German Interdisciplinary Taskforce for Clinical Hemotherapy (IAKH). The group was charged with proposing simple criteria to be used by hemovigilance systems to document instances of OT. Results This international initiative combined a narrative review of the literature for the rate and outcomes of OT with transfusion error reports to propose a definition for OT, including a definition for transfusion-induced hypercoagulopathy (TIH), three new codes for OT/TIH and subcodes A to G, three severity categories (serious adverse event, adverse event, near miss), and four incident codes (definite, probable, possible, not determinable). These codes can be used by hemovigilance systems to appropriately document instances of OT. Conclusions Global adoption of these codes within hemovigilance systems would assist with the recognition and reporting of instances of OT, promote effective policies for adequate clinical administration techniques, and support technical guidelines for avoidance of OT. Thereby, incorporation of OT into hemovigilance strategies could support adequate use of blood products, increase patient safety, and facilitate blood supply and availability.
Erstmals veröffentlicht: 09. Dezember 2024
Gesehen am 24.03.2025